Consecutive Case Study of Detraining On Some Functional, Physical, Body and Compound Skills Variables In Advance Basketball Players - Taha, Ahmed; Hanoon, Wasan (Journal of Physical Education, 2020)
The study aimed at finding scientific results of stopping training on speed endurance through a consecutive study conducted on advanced basketball players for the period of (8 weeks). The researchers used the experimental method on (15) advanced basketball players from Baghdad clubs season 2018-2019. The average age was (22.867)(SD ±2.455), their average length was (189.533) (SD ±8.228), and the average weight was (24.316) (SD ±2.455). The first test was conducted immediately after the end of the league, the second test after 4 weeks from the first test, and the third after 4 weeks from the second test. In other words, the total period of stopping training is (8 weeks). The data was collected and treated using proper statistical operations to conclude that stopping training affected many physical variables including speed endurance during stopping training for 4 weeks.  In addition to that the researchers concluded that stopping training have an effect on distant in YoYo test and speed endurance in the first (4) weeks.